Effects of stocking density on growth of channel catfish, Ictalurus punctatus, fingerlings in Southern Brazil - Esquivel, Betina M.; Esquivel, Juan R. [UNESP]; Zaniboni F., Evoy (Taylor & Francis, 1997)
Channel catfish, Ictalurus punctatus, fingerlings (mean length: 4.0±0.5 cm) were stocked into sixteen 16-m2 tanks with cement walls and earth bottoms. Four stocking densities were used: 10, 15, 20, and 25 fish/m2. Fish were fed a prepared diet containing 36% protein according to a fish size/water temperature-dependant chart for 120 days. Fish were stocked on January 20, 1992. Average water temperature varied from 19.7°C to 28.5°C. Final mean values of individual fish length and weight were significantly higher (P < 0.05) for the density of 10 fish/m2 and averaged 19.4±2.6 cm and 70.0±16.9 g, respectively. Food conversion ratio was significantly higher (P < 0.05) for fish stocked at rate of 25 fish/m2. Survival rates averaged 91.4%, with no significant differences (P > 0.05) found among treatments. These results demonstrate the viability of channel catfish fingerling growth in southern Brazil.